2016
DOI: 10.2109/jcersj2.16104
|View full text |Cite
|
Sign up to set email alerts
|

Processing of dielectric nanocube 3D-assemblies and their high electrical properties for next-generation devices

Abstract: Nanocrystals have great potential to achieve extremely high electrical properties induced by their shapes, size, and facet surfaces. BaTiO 3 nanocube (BT NC) 3D-assemblies with numerous interfaces and closely packed nanostructure are attracting as materials for next-generation dielectric devices due to their advantages for enhancing dielectric properties such as high packing density, high orientation, and interaction of the interfaces between the nanocubes. In this paper, we review our studies on the solutionb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…5 particle sizes) 89,90 . However, dense multilayered superlattice assemblies of BaTiO 3 nanocubes 29,84,[91][92][93] were also produced in some experiments, where the kinetic effects have been systematically controlled. The surface and inner structure were highly ordered with SC lattice and a packing fraction up to 90% 29,94 over a relatively large area of up to ∝ 10 µm 2 84,91,93,95 with thickness varying from several hundred nanometers 29,84,94 up to a ∝ 1 µm 95 (several examples are shown in Fig.…”
Section: Nanoperovkite Cubesmentioning
confidence: 99%
“…5 particle sizes) 89,90 . However, dense multilayered superlattice assemblies of BaTiO 3 nanocubes 29,84,[91][92][93] were also produced in some experiments, where the kinetic effects have been systematically controlled. The surface and inner structure were highly ordered with SC lattice and a packing fraction up to 90% 29,94 over a relatively large area of up to ∝ 10 µm 2 84,91,93,95 with thickness varying from several hundred nanometers 29,84,94 up to a ∝ 1 µm 95 (several examples are shown in Fig.…”
Section: Nanoperovkite Cubesmentioning
confidence: 99%
“…To develop thinner high-performance smartphones and wearable devices, such as eyeglass-type and wristwatch-type, miniaturization and improvement of the properties of dielectric devices such as multilayer ceramic capacitors (MLCCs) are required. An ordered assembly of BaTiO 3 nanocubes (nanocrystals) is a candidate as the main component of such devices [1][2][3][4][5][6][7][8][9][10]. The size of a BaTiO 3 nanocube is about 15 nm, which is much smaller than the typical BaTiO 3 -based particles of about 100 nm in diameter currently used in MLCCs [5,6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of previous studies have reported using platinum (Pt) 11 and palladium (Pd) 12 nanocubes as a base substance; however, the strain between the BaTiO 3 nanocubes led to a high dielectric constant in the densely assembled ceramic. 13 That is, BaTiO 3 nanocubes are necessary for the material design because of the surface properties of the particles. The synthesis of BaTiO 3 nanoparticles requires three key points: (1) a method to control the particle size because nanoscale materials are desirable as a consequence of their large specific surface area; (2) a method to control the particle shape because cubes are desirable as a consequence of the wide contract area between nanocubes; and (3) a method to control the particle surface as strain between nanocubes is desirable because it eliminates the need for a dispersant or surfactant.…”
Section: Introductionmentioning
confidence: 99%